Textological Features of Yakut Olonkho in the Viluy Expedition Field: Research Records of A.A. Savvin and M.N. Zhirkov - Danilova, Anna Nikolaevna; Larionova, Anna Semyonovna (Journal of History Culture and Art Research, 2018)
The article gives an insight into the textological features of the manuscripts, collected by A.A. Savvin during his Viluy expedition of 1938. The analysis of the manuscript materials, in particular, the olonkho manuscripts “Tebet Menik bogatyr”, allowed singling out the main principles and methods of collecting epic works, which were implemented during the Viluy folklore expedition. The olonkho manuscript “Tebet Menik bogatyr” is stored in the Manuscript Collection Fund of the Yakut Research Center of the Siberian Branch of the Russian Academy of Sciences and it is one of the best examples of the Viluy local tradition. This is justified by the archaic motif of the hero’s birth from elderly parents. In the course of study of the fixed poetic constructions, a natural input of curses, well-wishing, proverbs and sayings text fragments into the olonkho structure, all of which perform the functions of putting together an epic formula and describing places typical for olonkho. There is additional biographical data about the famous Yakut olonkhosut (olonkho teller), S.I. Eremeyev – Dedeges. The present study analyzes the methods and approaches to field research in process of recording the olonkho songs during the Viluy expedition organized by M.N. Zhirkov in 1943. We have selected notes text corpus of this expedition, which is stored at the A.S. Pushkin National Library of the Sakha Republic (Yakutia). We analyzed records of the characters’ chants, which are typical for the Yakut olonkho and we are making a hypothesis on the type of Viluy region olonkho they could possibly belong to. We also give a comparative analysis of the chants by a Tungus bogatyr Ardzhyamaan-Dardzhyamaan in the olonkho by S.A. Zverev – Kyyl uola from the Nurbinsky Ulus (Region) and Ivan Borisov from the Verkheviluysky Ulus (Region). It was determined that even within the regional performing styles, which the Viluy chanting style belongs to, there is a possible existence of local regional singing (performing) styles: in this case, the Nurbinsky and Verkhneviluysky regional traditions are implied.